Library and Information Science Education and Training in Uganda : Trends, Challenges, and theWay Forward - Okello-Obura, Constant; Kigongo-Bukenya, I. M. N. (Education Research International, 2011)
In today′s public and private sectors, corporate governance is a key focus, and management of libraries, records, archives, and information centers is an increasingly important preoccupation. This implies that the issue of LIS education should not be taken lightly. As the economy grows, the demand for information will propel the demand for LIS professionals because of the need to manage different kinds of documents. This paper, based on relevant literature review and the authors′ experience as LIS practitioners and educators, aims at discussing this subject and highlights important issues to be addressed. The paper makes a brief exploration of LIS education in Uganda, identifies the challenges, and proposes strategies as the way forward. It recommends that as LIS education and training seeks a wider role in society, there is a need to prepare students for careers in a rapidly changing world. This requires multidisciplinary education, greater emphasis on core knowledge, and fully well‐articulated graduate programmes to meet the requisite of LIS professionals.